New methodological approach for distancing the takeoff point further from the bar when high jumping using the flop technique - Watanabe, T. (Japan Journal of Physical Education, Health and Sport Sciences, 2014)
Taking off too near the bar in high jumping may cause injuries to the ankle or knee of the takeoff leg and make it difficult for jumpers to utilize their approach speed. These results lead to performance reduction eventually but no methodological approach for solving this problem has yet been presented in the relevant literature. The purpose of this study was to propose a new methodological approach for distancing the takeoff point further from the bar when high jumping using the flop technique, based on phenomenological analysis of two coaching cases in which a new training approach successfully solved this problem. The technical problem of taking off too near the bar might not be solved by relocating the starting point of approach run further back. With such a methodological approach, jumpers often feel a sense of "distance," which automatically makes them extend their stride length on the approach, so that they take off at the usual takeoff point relative to the bar. Additional relocating of the starting point further back, which is beyond the scope of this automatic adjustment of stride length, prevents jumpers from performing the flop technique. The author adopted a new methodological approach during coaching of a female junior high school student who was facing the above technical problem. This methodological approach consisted of four learning steps. The first learning step was to perform the flop technique using an almost straight approach run from a frontal direction in relation to the bar, and the last step was performing the new target technique with a further takeoff point. The other two intermediate steps were to assist this transition. With this methodological approach, she was able to modulate her sense of distance first, and then she succeeded in distancing her takeoff point further from the bar. This technical change also allowed her to properly utilize her approach speed. During coaching of another female junior high school student who faced the same technical problem, the author adopted almost the same methodological approach, so that she also quickly succeeded in distancing her takeoff point further from the bar. Phenomenological analysis of these coaching processes suggested that this new methodological approach can be used for distancing the takeoff point further from the bar when high jumping using the flop technique.